2022
DOI: 10.3390/su14137889
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Research in Tourism and Hospitality Field: A Bibliometric and Visualization Analysis

Abstract: New studies have constantly been emerging in the field of tourism. However, it is not clear to what extent which study contributes to the literature and tourism application areas. There are a few bibliometric studies that illustrate the intellectual structure of the tourism innovation field. Therefore, the purpose of this study is to determine the performance and intellectual structure of research studies conducted on innovation in the field of tourism. For this purpose, a bibliometric analysis of 387 research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 81 publications
(144 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, researches point out to the need of investment into innovations in tourism concerning the economics of experience and behaviour culture of consumes as well as knowledge sharing . More recent findings of a similar research on the topic of tourism and innovations, i.e., a bibliometric review of findings (Işik et al, 2022), show further growth of research papers and citations in this field. One of the breakthroughs enabled by innovations in tourism concerns the personalization of tourism services and the related visitors' typology.…”
Section: Eusair and Innovationmentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, researches point out to the need of investment into innovations in tourism concerning the economics of experience and behaviour culture of consumes as well as knowledge sharing . More recent findings of a similar research on the topic of tourism and innovations, i.e., a bibliometric review of findings (Işik et al, 2022), show further growth of research papers and citations in this field. One of the breakthroughs enabled by innovations in tourism concerns the personalization of tourism services and the related visitors' typology.…”
Section: Eusair and Innovationmentioning
confidence: 62%
“…Namely, tourists today increasingly seek a high level of security and quality where innovations play a key role (Gkoulgkoutsika et al, 2022). Some authors are going even further pointing to the impact of COVID-19 pandemic to necessary shift towards the innovations related to sustainability and use of new technologies that significantly contribute to the quality of tourism offer and are a competitive advantage on the tourism services market (Işik et al, 2022). Innovations in tourism are not only development opportunities but are also a challenge, i.e., potential risk for entrepreneurs.…”
Section: Eusair and Innovationmentioning
confidence: 99%
“…The author will utilize bibliographic research based on bibliometric and visualization analyses in future, following important research initiatives [74][75][76]. The case study offers the required information about the needs in creating similar tools.…”
Section: Resultsmentioning
confidence: 99%
“…Such findings emphasize the importance of institutional support in fostering impactful environmental innovation research as confirmed by other bibliometric studies. [51][52][53] The locations of the contributing organizations are displayed in Table 6. The People's Republic of China (197, 19.14%) and England (230, 14.82%) provide significantly larger contributions than any other country.…”
Section: Authors Affiliationmentioning
confidence: 99%